Theory on the Theoretical Analysis of Ghafur Ghulam's Creation (Eurasian Research Bulletin, 2024)
Theoretical analysis of Ghafur Ghulam's creation can provide valuable insights into the themes, styles, influences, and impacts of his works on literature and society. By delving into the theoretical underpinnings behind Ghafur Ghulam's creations, scholars and readers can gain a deeper understanding of the cultural, societal, and historical contexts in which his works are situated. This type of analysis aims to explore not just what the works say on the surface but also the underlying structures, symbols, and meanings embedded within them.